1996
DOI: 10.1097/00007890-199610150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Capsule Diameter, Adequacy of Encapsulation, and Survival of Microencapsulated Rat Islet Allografts1

Abstract: As a consequence of its large volume, a microencapsulated islet graft can be implanted only into the peritoneal cavity. The graft volume can be reduced by using small capsules. However, reduction of the diameter of the capsules holds a certain risk, because with smaller capsules, more islets may be found to protrude from the capsules. We have developed a lectin binding assay which, after encapsulation, specifically labels islets or parts of islets that are insufficiently immunoprotected as a consequence of ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 21 publications
3
102
0
Order By: Relevance
“…Also, an inadequate mechanical integrity of the capsules [9,12] can cause immunological reactions in the recipient. Finally, we found that grafts can fail as the consequence of incomplete encapsulation of islets [13,14].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Also, an inadequate mechanical integrity of the capsules [9,12] can cause immunological reactions in the recipient. Finally, we found that grafts can fail as the consequence of incomplete encapsulation of islets [13,14].…”
Section: Introductionmentioning
confidence: 79%
“…Purification of alginate was performed as described in detail by our group elsewhere [8]. All identified factors influencing biological responses were tested in the present study [5,[8][9][10][11][12][13][14]. The composition of the alginate was studied after purification by nuclear magnetic resonance analysis [8].…”
Section: Alginatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequately encapsulated islets are identified by positive fluorescence (Fig. 3), and the overall adequacy of an islet encapsulation procedure can be quantified by expressing the number of inadequate capsules as the percentage of the total number of capsules containing islets [58,95].…”
Section: +mentioning
confidence: 99%
“…The literature reveals, however, that success has so far been limited and non-reproducible. It is thought that the inability of encapsulated islet grafts to reproducibly achieve and maintain long-term euglycaemia is related not only to insufficient immunoprotection, but also to a variety of technical and metabolic issues, including: the encapsulation process, composition/purity of the microcapsule [12], capsule size and surface structure [13,14], poor biocompatibility [15,16], and endotoxin levels of the alginate [17,18]. Furthermore, while the addition of poly-L-lysine has been used to reduce capsule porosity [19], its addition has resulted in an increased fibrotic response [15].…”
Section: Introductionmentioning
confidence: 99%